Exploring the relationship between emotional intelligence, transformational leadership and their impact on operational effectiveness in multi-sectoral organizations (2020)
This investigation seeks to evaluate/explore the relationship between two variables of Emotional Intelligence (EI); use of emotions (UOE) and other's emotion appraisal and recognition (OEA), along with Transformational Leadership (TL) and their impact on the Operational Effectiveness (OE) of multisectoral organizations in Valle del Cauca region. The instrument used to measure UOE, OEA and OE was an adaptation of Santa et al. (2019) and Tidd et al. (2013) questionnaire. And for TL the CELID questionnaire was applied (Castro, Nader & Casullo, 2004). 130 answers were collected and for the statistical analysis, Structural Equation Modelling (SEM) was used to test the hypothesis and interaction of the variables. Results show that Transformational Leadership is closely tied to Emotional Intelligence, and even though the latter shows no direct impact on Operational Effectiveness, Transformational Leadership does influence how effective organizations can be. This hints at indirect interactions between all 3 variables that merit further study.